2017
DOI: 10.1002/term.2431
|View full text |Cite|
|
Sign up to set email alerts
|

GDNF Schwann cells in hydrogel scaffolds promote regional axon regeneration, remyelination and functional improvement after spinal cord transection in rats

Abstract: Positively-charged oligo[poly(ethylene glycol)fumarate] (OPF ) is a biodegradable hydrogel used for spinal cord injury repair. We compared scaffolds containing primary Schwann cells (SCs) to scaffolds delivering SCs genetically modified to secrete high concentrations of glial cell-derived neurotrophic factor (GDNF). Multichannel OPF scaffolds loaded with SCs or GDNF-SCs were implanted into transected rat spinal cords for 4 weeks. GDNF-SCs promoted regeneration of more axons into OPF scaffolds (2773.0 ± 396.0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…Our primary study focus was to determine the combinatorial or additive effects between the drug and implanted cells, rather than between the drug in empty scaffolds. We have consistently shown than MG‐only scaffolds are capable of supporting a rate of axonal regeneration that is approximately 80% less than that seen with SC‐implanted scaffolds without drug elution (Chen et al, ; Hakim et al, ; Madigan et al, ). The effect of rapamycin on astrocytes, including on astrocyte infiltration into the scaffold and on astroglial scar formation, was also not assessed in the current study, and represents another important limitation in the clarification of mechanisms behind the observed functional improvement.…”
Section: Discussionmentioning
confidence: 73%
“…Our primary study focus was to determine the combinatorial or additive effects between the drug and implanted cells, rather than between the drug in empty scaffolds. We have consistently shown than MG‐only scaffolds are capable of supporting a rate of axonal regeneration that is approximately 80% less than that seen with SC‐implanted scaffolds without drug elution (Chen et al, ; Hakim et al, ; Madigan et al, ). The effect of rapamycin on astrocytes, including on astrocyte infiltration into the scaffold and on astroglial scar formation, was also not assessed in the current study, and represents another important limitation in the clarification of mechanisms behind the observed functional improvement.…”
Section: Discussionmentioning
confidence: 73%
“…Different types of biomimetic synthetic scaffolds have previously been compared and demonstrated that OPF+ supports the most robust axonal regeneration . Schwann cells produce the extracellular microenvironment that supports regeneration of CNS axons and promote regeneration in OPF+ scaffolds (Chen et al 2017;Olson et al 2009). Fibrosis and a foreign body response to SC-loaded OPF+ scaffolds were identified as a major remaining barrier to axon regeneration and functional recovery (Hakim et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Scores for the left and right hind limbs were then averaged to obtain the overall BBB score for each animal, which was used for statistical analyses. As in previous our previous studies (Chen et al 2017;Hakim et al 2015) any animal with a BBB score greater than 4 (representing slight movement of all three joints of the hind limb) at one week post implantation was considered to have a physiologically incomplete transection and was excluded from further functional analysis. A total of 10 rats distributed across all groups from both cohorts were excluded in this way (Table 1).…”
Section: Open Field Hind Limb Locomotor Function Testingmentioning
confidence: 99%
See 2 more Smart Citations